(3QaY GdMLH GdeSJhQI Yf eMGSf GdebUhQIs - (3CHi GdbGSe eMeO Hf CMeO Hf eMeO GdMSjfj GdSHJis; (3MGRe GdbQWGLfj , MGRe Hf eMeO Hf MSf Hf MGRe, CHh GdMSf,J (B684 (3g` s
(3ChdgG (B:s
(3hHYO aEfi deG JCedJ ebUhQI GdEeGe GdChMO CHj GdMSf GdaJjgG JLeY VQhHG ef GdEMSGf hJTJed Ydi CaGfjf ef GdHjGf s
(3BNQgG (B:s
(3hGJjJ HeG jMUd efg GdbGQF Ydi QTGO abO hajJ HeG hYOJ s
(3bSeGfs
(3fSNI NGeSI JJab ai ChdgG eY GdfSNI GdChdi HGNJdGa ai HYV GdCdaGX HBNQ UaMGJgG JYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B159s
Keywords: (3GdCOHs